2018
DOI: 10.1002/acn3.600
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory and auditory deviance detection for outcome prediction during postanoxic coma

Abstract: ObjectiveProminent research in patients with disorders of consciousness investigated the electrophysiological correlates of auditory deviance detection as a marker of consciousness recovery. Here, we extend previous studies by investigating whether somatosensory deviance detection provides an added value for outcome prediction in postanoxic comatose patients.MethodsElectroencephalography responses to frequent and rare stimuli were obtained from 66 patients on the first and second day after coma onset.ResultsMu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(87 reference statements)
0
10
0
Order By: Relevance
“… 52 Interestingly, based on the concept of auditory discrimination in MMN, some authors have tried to explore DOC with sensory discrimination. In the study of Pfeiffer et al, 53 patients with postanoxic DOC underwent an auditory discrimination paradigm and then a sensory discrimination paradigm. The somatosensory discrimination paradigm consisted in a vibrotactile stimulation on the left index finger (standard stimulus of 100 ms and deviant stimulus of 150 ms) presented in a pseudorandom order in two blocks with 80% of standard stimuli and 20% of deviant stimuli.…”
Section: Mmnmentioning
confidence: 99%
“… 52 Interestingly, based on the concept of auditory discrimination in MMN, some authors have tried to explore DOC with sensory discrimination. In the study of Pfeiffer et al, 53 patients with postanoxic DOC underwent an auditory discrimination paradigm and then a sensory discrimination paradigm. The somatosensory discrimination paradigm consisted in a vibrotactile stimulation on the left index finger (standard stimulus of 100 ms and deviant stimulus of 150 ms) presented in a pseudorandom order in two blocks with 80% of standard stimuli and 20% of deviant stimuli.…”
Section: Mmnmentioning
confidence: 99%
“…The vast majority of deviance studies in coma target the auditory pathway, with the exception of one study comparing auditory and somatosensory stimuli, using the same oddball paradigm ( Pfeiffer et al, 2018 ). Interestingly, this study found that discrimination between deviant and standard events at the EEG level is preserved in acute coma for both the auditory and somatosensory modalities.…”
Section: Disorders Of Consciousnessmentioning
confidence: 99%
“…Moreover, while the global effect was not in itself predictive of the patient's outcome, an improvement in decoding global standard vs. global deviant stimuli over the first 2 days of coma was informative of survival and return of consciousness (Tzovara et al, 2015). The vast majority of deviance studies in coma target the auditory pathway, with the exception of one study comparing auditory and somatosensory stimuli, using the same oddball paradigm (Pfeiffer et al, 2018). Interestingly, this study found that discrimination between deviant and standard events at the EEG level is preserved in acute coma for both the auditory and somatosensory modalities.…”
Section: Auditory Predictions and Their Link To Coma Outcomementioning
confidence: 99%
“…Only the electrodes from the 10-20 system were considered in the present study. Recordings in Bern were performed in the context of a research project involving a mismatch negativity paradigm [20,21], after which 10 minutes of baseline EEG and then EEG during stimulations were recorded. Traces were not available to treating clinicians, however a minority of patients underwent an additional EEG shortly before or after the study EEG in case of clinical suspicion of seizures.…”
Section: Eeg Recordingsmentioning
confidence: 99%